StpA and the regulation of OmpF porin expression in Escherichia coli - Deighan, Padraig (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2001)
When the proteomic profile of a wild-type strain of Escherichia coli and its stpA hns mutant derivative were compared by two-dimensional gel electrophoresis, the levels of expression of several proteins were altered. One of these, which was strongly down-regulated in the absence of the regulatory proteins StpA and H-NS, was identified as the outer membrane porin protein, OmpF. In this study, the molecular details of how StpA and H-NS control OmpF porin expression were examined.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin